Case report: Efficacy and safety of regorafenib plus fluorouracil combination therapy in the treatment of refractory metastatic colorectal cancer - Haque, Emaan; Muhsen, Ibrahim N.; Esmail, Abdullah; Umoru, Godsfavour; Mylavarapu, Charisma; Ajewole, Veronica B.; Abdelrahim, Maen (Frontiers in Oncology, 2022)
Background More than half of patients with colorectal cancer (CRC) present with metastatic disease or develop recurrent disease on first-line and second-line options. Treatment beyond the second line remains an area of unmet need for patients with progressive or recurrent disease. Methods We retrospectively reviewed data of adult (>18 years old) patients with mCRC who received regorafenib + 5FU combination therapy at Houston Methodist Hospital with outcomes of interest including response rate, discontinuation due to side effects, and overall survival. Results Seven patients received regorafenib + 5FU combination therapy for mCRC after receiving at least two other lines of therapy (including at least one fluorouracil-based therapy). Four patients (57%) achieved disease control in 7-12 weeks after therapy initiation while three patients developed recurrent disease. In patients who achieved disease control, no new adverse events were reported among patients with this combination. Conclusion Regorafenib and Fluorouracil combination could be considered an option beyond the second line for patients with treatment-refractory metastatic colorectal cancer. Further studies, including a prospective trial, are needed to investigate the efficacy and safety of regorafenib plus 5FU therapy compared to other limited available therapies.